Relationship of qSOFA values to gastric perforation patients in A. W. Sjahranie General Hospital, Samarinda, Indonesia - ., Uwais; Nahusuly, Fritz; Sampetoding, Samuel (International Journal of Research in Medical Sciences, 2019)
Background: Authors hypothesized the qSOFA score would be useful in sepsis patients caused by gastric perforation. The present study investigated the relationship of qSOFA value to outcome of patients with gastric perforation in Samarinda. Methods: This research was analytical, descriptive research method using cross-sectional study design 70 patients. Data analysis was obtained to see the relationship between age, gender, vital sign qSOFA and survival in gastric perforation patients. Results: Mean systolic blood pressure was significantly higher in subjects who lived than those who died, i.e. 105.5 vs 92.5 (p <0.001). Mean diastolic blood pressure was significantly higher in subjects who lived than those who died, ie 80.0 vs 66.8 (p <0.001). The respiration rate was significantly lower in subjects who lived than those who died, namely 22.9 vs 24.6 (p <0.001). The mean GCS score was significantly higher in subjects who lived than those who died, ie 14.2 vs 12.2 (p <0.001). Conclusions: The higher the qSOFA score in the study subjects with gastric perforation, the higher the mortality rate. There was a relationship between the qSOFA value and the outcome of patients with gastric perforation where the mean qSOFA score was significantly lower in subjects who lived than those who died.